2010
DOI: 10.1016/j.cell.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The Exon Junction Complex Controls the Splicing of mapk and Other Long Intron-Containing Transcripts in Drosophila

Abstract: Signaling pathways are controlled by a vast array of posttranslational mechanisms. By contrast, little is known regarding the mechanisms that regulate the expression of their core components. We conducted an RNAi screen in Drosophila for factors modulating RAS/MAPK signaling and identified the Exon Junction Complex (EJC) as a key element of this pathway. The EJC binds the exon-exon junctions of mRNAs and thus far, has been linked exclusively to postsplicing events. Here, we report that the EJC is required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
137
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(153 citation statements)
references
References 79 publications
(94 reference statements)
13
137
2
1
Order By: Relevance
“…In Drosophila, it has been shown that the EJC components regulate the splicing of long-intron containing pre-mRNAs, and EJC KD reduced their expression more than short introncontaining pre-mRNAs [27]. We performed the same analysis with HeLa cell transcriptome data but found no correlation between intron length and differential expression level in any KD conditions in human cells (Additional file 17).…”
Section: Ejc Regulates Cassette Exons With Longer Flanking Intronsmentioning
confidence: 82%
See 1 more Smart Citation
“…In Drosophila, it has been shown that the EJC components regulate the splicing of long-intron containing pre-mRNAs, and EJC KD reduced their expression more than short introncontaining pre-mRNAs [27]. We performed the same analysis with HeLa cell transcriptome data but found no correlation between intron length and differential expression level in any KD conditions in human cells (Additional file 17).…”
Section: Ejc Regulates Cassette Exons With Longer Flanking Intronsmentioning
confidence: 82%
“…In addition, the EJC has been shown to be required for the splicing of mapk pre-mRNA and other long introncontaining pre-mRNAs in Drosophila [27,28], and two recent studies revealed that EJC components contribute to the splicing of weak intron 4 of the piwi transcript in Drosophila [29,30]. In Xenopus, eIF4A3 is also required for accurate splicing of ryanodine receptor pre-mRNA [31].…”
Section: Introductionmentioning
confidence: 99%
“…Once clamped onto mRNA, the tetrameric core acts as a platform to recruit multiple factors conferring different functions to the EJC as mRNA progresses from splicing to translation. Notably, the EJC contributes in regulating the splicing of specific transcripts (8)(9)(10) and participates in mRNA transport (11). The EJC also plays a major role in nonsense-mediated mRNA decay (NMD) that triggers the decay of aberrant mRNAs containing a premature termination codon (12).…”
mentioning
confidence: 99%
“…Pol II elongation rates and/or its CTD phosphorylation status might regulate exon tethering in a transcript-specific manner, thus facilitating processing of long intronic sequences. Intriguingly, as splicing of long introns in Drosophila is facilitated by components of the pre-exon junction complex (EJC) (Ashton-Beaucage et al 2010;Roignant and Treisman 2010), this complex might be involved in modulating exon tethering by Pol II in a transcriptspecific manner.…”
Section: Discussionmentioning
confidence: 99%